A STUDY ON THE SHARES OF SEVERAL INDEPENDENT VARIABLES IN PREDICTING THE DOMESTIC GAS PRICE - Andry Prima (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2016)
End users of natural gas have long waited for the government regulation on a more rational gas price. In 2017, the answer to the end users is the  new Energy and Mineral Resources Ministerial Decree number 434 K/12/MEM/2017  on the supervision of energy business activities, one of which is the natural gas sector. Prior to the stipulation, the price of natural could reach over $ 12 / MM BTU. Thus, the decree stipulates the price of natural gas should be $ 9,95 / MMBTU. This paper aims at capturing the closer profiles of variables that might have profound impact on the price of domestic natural gas. Analytical Data Tools used in this study are the IBM – SPSS and XLSTAT In the end, the study resulting the price range suggestion, that is in still in line with the government suggested price